PERBANDINGAN HUKUM ZINA DALAM HUKUM ISLAM DENGAN KUHP - Triadi Triadi (Ensiklopedia of Journal, 2023)
The concept of the Criminal Code was made by the legislature and formal legality has not been clearly regulated, for cases of adultery the principle of material legality can be used which allows a judge not only to base written law but law that lives in society can be used as a basis. Through the thinking of progressive jurists it is not impossible that the principle of material legality in Indonesia will turn into law that is recognized by the State and legislated as positive law. There needs to be firmness from law enforcement officials to achieve this goal and make Indonesian criminal law a tool for dealing with crimes including adultery. .Zina can be made into a criminal act and in the sense of having intercourse outside of marriage. Which refers to the laws that live in society and is carried out with material legality. Along with the progress experienced by society in various fields, legal regulations also increased. The addition of these legal regulations cannot be prevented because the community hopes that with the addition of these regulations, life and safety will improve even though the number of violations against these regulations may increase. Based on the framework above, it appears that the crime of adultery according to positive law and according to Islamic law, has quite fundamental differences, so research is needed to find out this so that it is hoped that it can be used as another alternative in carrying out criminal law reforms in Indonesia in the future.Keywords: Comparative Law, Adultery, Islamic Law, Criminal Code.